INTER-HOSPITAL TRANSFER OF TRAUMA PATIENTS IN A DEVELOPING COUNTRY: A PROSPECTIVE DESCRIPTIVE STUDY - Verma, Vikas; Singh, Girish Kumar; Calvello, Emilie J B; Kumar, Santosh; Singh, Chandra Mani; Harjai, Mamta (Indian Journal of Community Health, 2013)
Introduction: During interhospital transfer patients are at risk due to possibility of serious complications. There are no guidelines governing the transfer of injured patients in India. It is important to identify the extent of the problem in the transfer process of the injured transferred to the trauma centre.Methods: On arrival in the Emergency Department patients were assessed for clinical status and the Glasgow Coma Score (GCS). The transfer vehicle was evaluated and the accompanying transfer personnel was interviewed to record details of the transfer process, training of the transfer personnel, adequacy of the transfer vehicle and its outfitted monitoring equipment. Data communicated to the trauma centre from the referring hospitals were also collected from the transfer records. The transferred group was compared to the non-transferred group.Results: Of the 592 patients admitted, 572 consented to the study. 327 were referred patients and 245 were directly admitted patients. Patients referred from peripheral hospitals had significantly lower GCS, higher ISS, higher admission gap and longer duration of hospital stay. The date and time of injury was documented in none of the referred patients, referral time in 44 (13.71%) cases, pulse rate in 110(34.38%) patients, blood pressure in 112 (34.25%) cases. The request for transfer was made in only 3 (0.93%) cases. Twelve cases (3.66%) were accompanied by a paramedic or a nurse. Intravenous access and infusions in progress were present in 192/327 (58.71%) transferred patients. Urethral catheters were present in 49 (15.17%) patients. Only 9/327 (2.79%) transferred patients had hard cervical immobilization. Hypotension at admission defined as a systolic BP < 120mm of Hg was present in 106 referred admitted cases. Conclusion: This study suggests that the injured patients are not being transferred in a manner that is consistent with evidence based guidelines which are known to minimize the known hazards of transfer process and consequently improve outcome. Despite the efforts being made, the condition as of now is unacceptable and needs a rational referral policy contributed to and agreed by all service providers which must be strongly enforced without delay.